Engineered aligned endothelial cell structures in tethered collagen hydrogels promote peripheral nerve regeneration. (May 2021) - Muangsanit, Papon; Roberton, Victoria; Costa, Eleni; Phillips, James B.
Abstract: Vascularisation is important in nerve tissue engineering to provide blood supply and nutrients for long-term survival of implanted cells. Furthermore, blood vessels in regenerating nerves have been shown to serve as tracks for Schwann cells to migrate along and thus form Bands of Büngner which promote axonal regeneration. In this study, we have developed tissue-engineered constructs containing aligned endothelial cells, or co-cultures of both endothelial cells and Schwann cells to test whether these structures could promote regeneration across peripheral nerve gaps. Type I rat tail collagen gels containing HUVECs (Human Umbilical Vein Endothelial Cells, 4 × 10 6 cells/ml) were cast in perforated tethering silicone conduits to facilitate cellular self-alignment and tube formation for 4 days of culture. For co-culture constructs, optimal tube formation and cellular alignment was achieved with a ratio of 4:0.5 × 10 6 cells/ml (HUVECs:Schwann cells). An in vivo test of the engineered constructs to bridge a 10 mm gap in rat sciatic nerves for 4 weeks revealed that constructs containing only HUVECs significantly promoted axonal regeneration and vascularisation across the gap, as compared to conventional aligned Schwann cell constructs and those containing co-cultured HUVECs and Schwann cells. Our results suggest that tissue-engineered constructs containing aligned endothelial cells within collagen matrix could be good candidates to treat peripheral nerve injury. Statement of significance: Nerve tissue engineering provides a potential way to overcome the limitations associated with current clinical grafting techniques for the repair of severe peripheral nerve injuries. However, the therapeutic cells within engineered nerve tissue require effective vascularisation in order to survive. This work therefore aimed to develop engineered nerve constructs containing aligned tube-like structures made from endothelial cells. Not only did this provide a method to improve vascularisation, it demonstrated for the first time that aligned endothelial cells can outperform Schwann cells in promoting nerve regeneration in the rat sciatic nerve model. This has introduced the concept of developing pre-vascularised engineered nerve tissues, and indicated the potential usefulness of endothelial cell structures in tissue engineering for peripheral nerve repair. Graphical abstract: Image, graphical abstract